Hubungan amalan e-kerajaan dengan prestasi organisasi kerajaan tempatan di Malaysia - Rohana, Husin (2019)
e-Government is a common managerial practice among the public sector to enhance its organizational performance. However, there are many barriers faced by the public sector in implementing the e-government. Hence, a research framework has been developed to address this issue. The purpose of this study is to examine the influence of e-Government towards the performance of Malaysia’s local government as mediated by organizational information technology (IT) capability. The study also examines the moderating effect of Total Quality Management (TQM) on the relationship between organizational IT capability and organizational performance. The motivation of this study is driven by the inconsistent dimensions applied in the research of e-Government which led to various differing results in terms of the performance of local governments. Due to these inconsistencies, the effect of possible mediating and moderating variables have been proposed to explain the inconsistencies. For the purpose of testing the research framework, a quantitative approach using the survey method was employed. A total of 108 questionnaires were distributed to Malaysian local government organizations with an 83% respond rate return. Data was analyzed using PLS-SEM technique. The results show the need for organizational IT capability in implementing e-Government to contribute in improving organizational performance. Test of mediation effect indicates that the organizational IT capability acts as a full mediator towards the relationship between e-Government and organizational performance, but this is not applicable to TQM, however, as it is proven that the latter could not act as a moderating variable. More importantly, this study also finds that technical IT infrastructure and human IT infrastructure are crucial elements to increase e-Government effectiveness. The findings are expected to contribute toward the enrichment of the knowledge on e-Government in the academic field. In particular, the research findings could become a guideline in the operation of local governments to be more efficient and effective in providing services to the local community.